2013
DOI: 10.5694/mja13.10036
|View full text |Cite
|
Sign up to set email alerts
|

Medical graduates becoming rural doctors: rural background versus extended rural placement

Abstract: For the three cohorts studied, rural clinical training through extended placements in rural clinical schools had a stronger association than rural background with a preference for, and acceptance of, rural internship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 8 publications
2
72
1
4
Order By: Relevance
“…The funding is directed for medical schools to: select students from rural areas, provide rural apprenticeship and internship for all medicine students and the perfect the support system for rural medicine students and teachers 17 . Amogst the goals of the RCTS are: 25% of medicine students to perform at least one year of their clinical training in a rural area and 25% of Commonwealth funded students to come from rural areas.…”
Section: Australiamentioning
confidence: 99%
“…The funding is directed for medical schools to: select students from rural areas, provide rural apprenticeship and internship for all medicine students and the perfect the support system for rural medicine students and teachers 17 . Amogst the goals of the RCTS are: 25% of medicine students to perform at least one year of their clinical training in a rural area and 25% of Commonwealth funded students to come from rural areas.…”
Section: Australiamentioning
confidence: 99%
“…O RCTS tem como objetivo financiar as escolas médicas australianas para o fortalecimento da formação de clínicos nas áreas rurais, através de fundos do governo. 19 O governo financia as escolas médicas, através da seleção de alunos oriundos de áreas rurais, provimento de estágios e internato rural. 20 Estabelecendo percentuais, como 25% dos estudantes de medicina realizam no mínimo um ano de sua formação clínica em uma área rural; 25% dos estudantes financiados pela Commowealth devem ser oriundos de áreas rurais; 90% das escolas médicas da Austrália participam deste programa.…”
Section: Experiências Internacionaisunclassified
“…3 The reasons for this are undoubtedly complex, but recent data suggest that longitudinal integrated clinical placements in rural settings have a greater impact than prior background in determining subsequent career and location choices. 4 The duration of rural exposure is of considerable importance, 5 with longer, voluntary rural placements more likely to influence rural career choices. 6 It has been demonstrated that both voluntary and compulsory rural terms can have a positive influence on subsequent career choice.…”
Section: Introductionmentioning
confidence: 99%